The Synthesis of Indonesian Socialism According to The Constitution - Aurora Jillena Meliala; Jonathan Andre Woods (Constitutionale, 2022)
This article is aimed to narrate the core value of the Indonesian economic system as stipulated by the founding fathers. It was called Ekonomi Kerakyatan (Proletarian Economy), introduced by Muhammad Hatta. It is also a distinctive feature of Indonesian democracy. A system that is centered on people’s empowerment. The Indonesian “third way” was introduced long before Giddens’s idea and it was claimed as authentic Indonesian socialism. One that is rooted in the value of Pancasila as Indonesia’s Weltanschauung  (Philosophische- Grondslag). A People-centered economy based on cooperativism and kinship. The paper used a qualitative method in its research. The first part will explain how Ekonomi Rakyat was defined and postulated under the Indonesian Constitution. Then, it will explain the transformation of the economic legislature and its implication for national development. Lastly, the resolution to reinvigorate the idea of a people-centered economy in Indonesian Economic Democracy and Legal framework is explained. The research finds that Indonesia’s inherent economic system is yet to be implemented in the national legal life and dramatically impacts the nation’s notions of prosperity. In the end, the research concludes that the economic system should be narrated in a sound legal framework, while the legal drafting and enforcement process depends on political commitment.